Fringe pattern analysis for optical metrology : theory, algorithms, and applications - Servín, Manuel; Quiroga, J. Antonio; Padilla, J. Moisés (Wiley-VCH, 2014)
Fringe Pattern Analysis for Optical Metrology: Theory, Algorithms, and Applications The main objective of this book is to present the basic theoretical principles and practical applications for the classical interferometric techniques and the most advanced methods in the field of modern fringe pattern analysis applied to optical metrology. A major novelty of this work is the presentation of a unified theoretical framework based on the Fourier description of phase shifting interferometry using the Frequency Transfer Function (FTF) along with the theory of Stochastic Process for the straightforward analysis and synthesis of phase shifting algorithms with desired properties such as spectral response, detuning and signal-to-noise robustness, harmonic rejection, etc.